Effect of sub-MIC of vancomycin and clindamycin alone and in combination with ceftazidime on Clostridium difficile surface layer protein A (slpA) gene expression. (October 2017) - Zarandi, Ebrahim Rezazadeh; Mansouri, Shahla; Nakhaee, Nouzar; Sarafzadeh, Farhad; Moradi, Mohammad
Abstract: Clostridium difficile ( C.difficile ) infection is often established in the presence of antibiotics and probably antibiotics can influence surface layer protein A (slpA) expression as a colonization factor. The aim of this study is to evaluate the effect of vancomycin (VAN), clindamycin (CLI) alone and in combination with ceftazidime (CAZ) on slpA gene expression to determine whether such antibiotics can have any effect on slpA expression. About ∼10 6 CFU/mL was inoculated to medium containing an appropriate concentration of antibiotics alone and in combination. After 24 and 48 h incubation under anaerobic condition, 3 mL of culture was excluded and centrifuged in 8000 × g per 3 min. The pellet was washed and used for RNA extraction. The RNA extraction, Dnase I treatment and cDNA synthesis was performed by RNA extraction, Dnase I, and cDNA synthesis kits, respectively. The real–time PCR were carried out by sybrGreen methods and data were analyzed based on comparative ΔΔCT . All antibiotics alone and in combination, except VAN/CAZ in clinical isolate, decreased the level of slpA gene expression in the 24-h incubation. While the expression profile of slpA was different in the 48-h incubation period. The VAN and CLI decreased the slpA expression, although the template of expression is closed to control medium. CAZ alone and in combination increased slpA expression. C. difficile may down-regulate slpA expression in the early stages of growth in sub-inhibitory concentration of antibiotics. But, over time C. difficile increases or over expresses the slpA expression level. Consequently C. difficile binds strongly to epithelial cells and continues to survive in the presence of sub-MIC concentration of antibiotics. This effect is observed especially with regard to CAZ and probably other third generation cephalosporins or in combination therapy with VAN or CLI, which are prescribed in the clinic. CAZ can interfere with the anti-down regulatory feature of VAN, CLI, and maybe other antibiotics. Highlights: Antibiotics probably influence on slpA gene expression in C. difficile. Ceftazidime alone and in combination with vancomycin and clindamycin up-regulated slpA expression at 48 hours. Ceftazidime alone and in combination up regulate slpA gene and probably SlpA protein. Therefore C. difficile can bind strongly to the epithelial cells.